PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN BANK PERKREDITAN RAKYAT - Andriyan, Okky; Supatmi, Supatmi (UI Scholars Hub, 2010)
This research is aimed to find out the influence of Corporate Governance (CG) mechanisms to the banking financial performance. As a regulated industry, this research wants to prove that the banking financial performance can be influenced by CG mechanisms, not just its complience to the banking regulations. The samples in this research are the non-governmental rural banks (Bank Perkreditan Rakyat) in Central Java. The financial performance of the BPR is measured by the ratio of NPL, KPMM, LDR, and ROA. CG mechanisms are measured by its managerial ownerships, the proportion of the outside directors, and the number of board of directors (BOD), while the control variables are the size of the BPR and the firm age of the BPR. This research finds the CG mechanisms simultaneously influence the ratio of NPL, KPMM, and ROA. The managerial ownerships and the proportion of the outside directors partially also show a negative influence to the ratio of NPL and ROA, and the number of BOD in partial shows a negative influence towards the ratio of LDR.